2015
DOI: 10.1038/labinvest.2014.140
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol gallstone disease: focusing on the role of gallbladder

Abstract: Gallstone disease (GSD) is one of the most common biliary tract diseases worldwide in which both genetic and environmental factors have roles in its pathogenesis. Biliary cholesterol supersaturation from metabolic defects in the liver is traditionally seen as the main pathogenic factor. Recently, there have been renewed investigative interests in the downstream events that occur in gallbladder lithogenesis. This article focuses on the role of the gallbladder in the pathogenesis of cholesterol GSD (CGD). Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 101 publications
0
25
0
Order By: Relevance
“…Gallbladder conditions reportedly affect gallstone formation. 55 In fact, CCD loading in control mice induced a white cloudy gallbladder appearance (Supplementary Figure 1E and Figure 1E). Histologic analyses of the gallbladders from CCD-fed control mice showed that wall thicknesses were increased and that infiltration of inflammatory cells had occurred ( Supplementary Figure 6A and B).…”
Section: Hepatocyte-selective Knockout Of Hif1a Affects the State Of mentioning
confidence: 94%
“…Gallbladder conditions reportedly affect gallstone formation. 55 In fact, CCD loading in control mice induced a white cloudy gallbladder appearance (Supplementary Figure 1E and Figure 1E). Histologic analyses of the gallbladders from CCD-fed control mice showed that wall thicknesses were increased and that infiltration of inflammatory cells had occurred ( Supplementary Figure 6A and B).…”
Section: Hepatocyte-selective Knockout Of Hif1a Affects the State Of mentioning
confidence: 94%
“…However, recent studies have increased our knowledge of GB function and its essential role in the development of cholesterol gallstone disease. 37 Thus, when conducting future epidemiological studies, it may be preferable to analyze cholecystectomized and gallstone patients separately with regards to their risk for developing MetS.…”
Section: Cholecystectomy and Mets Componentsmentioning
confidence: 99%
“…[1] It is a multifactorial disease and has several risk factors including sex, age, genetic factors, race, obesity, rapid weight loss, diet, alcohol consumption, diabetes mellitus (DM), hyperlipidemia, drug use, and pregnancy. [2]…”
Section: Introductionmentioning
confidence: 99%